Influence of varying depth of cut and feed rate to tool wear rate and surface roughness in aluminium, mild steel and P20 tool steel - Nadirah, Ismail (2012)
Since the phenomenon of tool life still not fully understood although many research and case study have been done before, an investigation on the tool wear rate and surface roughness value being done for three types of workpiece material which are aluminium, mild steel and P20 while cutting tool that been used is carbide coated insert. The main reason for this investigation is to study and understand the behavior of cutting tool in order to determine the tool wear rate and tool life. From this investigation, surface roughness value for each type of workpiece material, Ra also can be collected. This investigation been done by applying high speed machining (HSM) concept, which high feed rate with light depth of cut.